MANAJEMEN KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PENDIDIKAN KARAKTER BUDAYA PEDULI LINGKUNGAN DI SMA NEGERI KOTA TERNATE - Kamisi, Mohtar; Wicaksono, Muhammad Arif (Jurnal GeoCivic, 2023)
This research is entitled School Principal Management in Implementing Environmentally Caring Cultural Character in State High Schools in Ternate City. This research aims to determine the management of school principals in a culture of environmental care in State Senior High Schools in Ternate City. School principal management has a very important role because every school must be able to instill the character of caring for the environment. The cultivation of character education must also be supported by the entire school community. The party who plays an important role in the environmental care character education program is the school principal. The program that has been decided must be able to be realized through the class teacher and introduced to students. Therefore, there are several indicators that must be achieved by each class in order to instill environmentally caring character education. The application of environmentally caring character values at Ternate City Public High School is carried out by building students' awareness to prevent damage to the natural environment around them, and developing efforts to repair natural damage that has occurred. Caring for the environment is a character that students must have. Environmentally caring character can reflect students' concern and sensitivity to their environment. Every school must be able to instill the character of caring for the environment.This research method uses descriptive research using a qualitative approach. Qualitative research is descriptive research that analyzes using an inductive approach. This research emphasizes the theoretical basis which serves as the focus of research when in the field. The location of this research will be carried out at Ternate City Public High School. The time for carrying out this research was carried out over six months from March to August 2023. The subjects of this research were the Principal, Deputy Head of Curriculum, Deputy Head of Student Affairs, and Teachers. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, and conclusions.The results of the research show that there is still a culture of caring for the environment in Ternate City State High School, there is a lack of student awareness regarding this, there are still students who throw rubbish carelessly, there are still students who damage the school garden and don't want to take responsibility, there are still students who don't care about the cleanliness of the school toilets. , there was rubbish in the classroom, rubbish was found in the school garden, water taps were still found that were not turned off after using them. This situation is very worrying because there are still many students who are not responsive and sensitive to their surrounding environment.Thus, the application of environmentally caring character values at Ternate City Public High School is carried out by building students' awareness to prevent damage to the natural environment around them, and developing efforts to repair natural damage that has occurred. Caring for the environment is a character that students must have. Environmentally caring character can reflect students' concern and sensitivity to their environment. Every school must be able to instill the character of caring for the environment.Keywords: Management, Principal, Character, and Environmental Care Culture